MAYBE Initial complexity problem: 1: T: (1, 1) f3(a, b, c, d) -> f1(0, b, c, d) (?, 1) f1(a, b, c, d) -> f2(a, b, c, e) [ b >= c ] (?, 1) f1(a, b, c, d) -> f2(1, b + 1, c, e) [ b + 1 = c /\ a = 0 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (1, 1) f3(a, b, c, d) -> f1(0, b, c, d) (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 Applied AI with 'oct' on problem 2 to obtain the following invariants: For symbol f1: -X_1 >= 0 /\ X_1 >= 0 This yielded the following problem: 3: T: (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] (1, 1) f3(a, b, c, d) -> f1(0, b, c, d) start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b, c, d) with all transitions in problem 3, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 ] We thus obtain the following problem: 4: T: (1, 2) f3(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 ] with all transitions in problem 4, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 2, c + 2, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 ] We thus obtain the following problem: 5: T: (1, 3) f3(a, b, c, d) -> f1(0, b + 2, c + 2, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 2, c + 2, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 ] with all transitions in problem 5, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 3, c + 3, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 ] We thus obtain the following problem: 6: T: (1, 4) f3(a, b, c, d) -> f1(0, b + 3, c + 3, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 3, c + 3, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 ] with all transitions in problem 6, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 4, c + 4, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 ] We thus obtain the following problem: 7: T: (1, 5) f3(a, b, c, d) -> f1(0, b + 4, c + 4, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 4, c + 4, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 ] with all transitions in problem 7, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 5, c + 5, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 ] We thus obtain the following problem: 8: T: (1, 6) f3(a, b, c, d) -> f1(0, b + 5, c + 5, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 5, c + 5, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 ] with all transitions in problem 8, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 6, c + 6, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 ] We thus obtain the following problem: 9: T: (1, 7) f3(a, b, c, d) -> f1(0, b + 6, c + 6, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 6, c + 6, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 ] with all transitions in problem 9, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 7, c + 7, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 ] We thus obtain the following problem: 10: T: (1, 8) f3(a, b, c, d) -> f1(0, b + 7, c + 7, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 7, c + 7, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 ] with all transitions in problem 10, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 8, c + 8, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 ] We thus obtain the following problem: 11: T: (1, 9) f3(a, b, c, d) -> f1(0, b + 8, c + 8, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 8, c + 8, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 ] with all transitions in problem 11, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 9, c + 9, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 ] We thus obtain the following problem: 12: T: (1, 10) f3(a, b, c, d) -> f1(0, b + 9, c + 9, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 9, c + 9, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 ] with all transitions in problem 12, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 10, c + 10, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 ] We thus obtain the following problem: 13: T: (1, 11) f3(a, b, c, d) -> f1(0, b + 10, c + 10, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 10, c + 10, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 ] with all transitions in problem 13, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 11, c + 11, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 ] We thus obtain the following problem: 14: T: (1, 12) f3(a, b, c, d) -> f1(0, b + 11, c + 11, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 11, c + 11, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 ] with all transitions in problem 14, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 12, c + 12, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 /\ c + 11 >= b + 13 /\ c + 11 >= b + 12 ] We thus obtain the following problem: 15: T: (1, 13) f3(a, b, c, d) -> f1(0, b + 12, c + 12, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 /\ c + 11 >= b + 13 /\ c + 11 >= b + 12 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 12, c + 12, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 /\ c + 11 >= b + 13 /\ c + 11 >= b + 12 ] with all transitions in problem 15, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 13, c + 13, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 /\ c + 11 >= b + 13 /\ c + 11 >= b + 12 /\ c + 12 >= b + 14 /\ c + 12 >= b + 13 ] We thus obtain the following problem: 16: T: (1, 14) f3(a, b, c, d) -> f1(0, b + 13, c + 13, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 /\ c + 11 >= b + 13 /\ c + 11 >= b + 12 /\ c + 12 >= b + 14 /\ c + 12 >= b + 13 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 13, c + 13, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 /\ c + 11 >= b + 13 /\ c + 11 >= b + 12 /\ c + 12 >= b + 14 /\ c + 12 >= b + 13 ] with all transitions in problem 16, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 14, c + 14, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 /\ c + 11 >= b + 13 /\ c + 11 >= b + 12 /\ c + 12 >= b + 14 /\ c + 12 >= b + 13 /\ c + 13 >= b + 15 /\ c + 13 >= b + 14 ] We thus obtain the following problem: 17: T: (1, 15) f3(a, b, c, d) -> f1(0, b + 14, c + 14, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 /\ c + 11 >= b + 13 /\ c + 11 >= b + 12 /\ c + 12 >= b + 14 /\ c + 12 >= b + 13 /\ c + 13 >= b + 15 /\ c + 13 >= b + 14 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 By chaining the transition f3(a, b, c, d) -> f1(0, b + 14, c + 14, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 /\ c + 11 >= b + 13 /\ c + 11 >= b + 12 /\ c + 12 >= b + 14 /\ c + 12 >= b + 13 /\ c + 13 >= b + 15 /\ c + 13 >= b + 14 ] with all transitions in problem 17, the following new transition is obtained: f3(a, b, c, d) -> f1(0, b + 15, c + 15, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 /\ c + 11 >= b + 13 /\ c + 11 >= b + 12 /\ c + 12 >= b + 14 /\ c + 12 >= b + 13 /\ c + 13 >= b + 15 /\ c + 13 >= b + 14 /\ c + 14 >= b + 16 /\ c + 14 >= b + 15 ] We thus obtain the following problem: 18: T: (1, 16) f3(a, b, c, d) -> f1(0, b + 15, c + 15, d) [ 0 >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ 0 = 0 /\ c + 1 >= b + 3 /\ c + 1 >= b + 2 /\ c + 2 >= b + 4 /\ c + 2 >= b + 3 /\ c + 3 >= b + 5 /\ c + 3 >= b + 4 /\ c + 4 >= b + 6 /\ c + 4 >= b + 5 /\ c + 5 >= b + 7 /\ c + 5 >= b + 6 /\ c + 6 >= b + 8 /\ c + 6 >= b + 7 /\ c + 7 >= b + 9 /\ c + 7 >= b + 8 /\ c + 8 >= b + 10 /\ c + 8 >= b + 9 /\ c + 9 >= b + 11 /\ c + 9 >= b + 10 /\ c + 10 >= b + 12 /\ c + 10 >= b + 11 /\ c + 11 >= b + 13 /\ c + 11 >= b + 12 /\ c + 12 >= b + 14 /\ c + 12 >= b + 13 /\ c + 13 >= b + 15 /\ c + 13 >= b + 14 /\ c + 14 >= b + 16 /\ c + 14 >= b + 15 ] (?, 1) f1(a, b, c, d) -> f1(0, b + 1, c + 1, d) [ -a >= 0 /\ a >= 0 /\ c >= b + 2 /\ c >= b + 1 /\ a = 0 ] start location: f3 leaf cost: 2 Complexity upper bound ? Time: 1.522 sec (SMT: 1.409 sec)